Branched glycopolymer prodrug-derived nanoassembly combined with a STING agonist activates an immuno-supportive status to boost anti-PD-L1 antibody therapy - Zhilin Li; Qianfeng Zhang; Zhiqian Li; Long Ren; Dayi Pan; Qiyong Gong; Zhongwei Gu; Hao Cai; Kui Luo (Elsevier, 2024)
Despite the great potential of anti-PD-L1 antibodies for immunotherapy, their low response rate due to an immunosuppressive tumor microenvironment has hampered their application. To address this issue, we constructed a cell membrane-coated nanosystem (mB4S) to reverse an immunosuppressive microenvironment to an immuno-supportive one for strengthening the anti-tumor effect. In this system, Epirubicin (EPI) as an immunogenic cell death (ICD) inducer was coupled to a branched glycopolymer via hydrazone bonds and diABZI as a stimulator of interferon genes (STING) agonist was encapsulated into mB4S. After internalization of mB4S, EPI was acidic-responsively released to induce ICD, which was characterized by an increased level of calreticulin (CRT) exposure and enhanced ATP secretion. Meanwhile, diABZI effectively activated the STING pathway. Treatment with mB4S in combination with an anti-PD-L1 antibody elicited potent immune responses by increasing the ratio of matured dendritic cells (DCs) and CD8+ T cells, promoting cytokines secretion, up-regulating M1-like tumor-associated macrophages (TAMs) and down-regulating immunosuppressive myeloid-derived suppressor cells (MDSCs). Therefore, this nanosystem for co-delivery of an ICD inducer and a STING agonist achieved promotion of DCs maturation and CD8+ T cells infiltration, creating an immuno-supportive microenvironment, thus potentiating the therapy effect of the anti-PD-L1 antibody in both 4T1 breast and CT26 colon tumor mice.